KEANEKARAGAMAN JENIS EKHINODERMATA DI PERAIRAN TELUK KUTA, NUSA TENGGARA BARAT - Yusron, Eddy (UI Scholars Hub, 2009)
Biodiversity of Echinoderms at Kuta Bay, West Nusa Tenggara. Observation on echinoderms diversity was carried out at coastal waters of Kuta bay in the Nusa Tenggara Barat, Nopember 2005. A total of 21 species of echinoderms, consist of 4 species Holothuroidea, 7 species Echinoidea, 5 species Asteroidea and 5 species Ophiuroidea have been found in the Kuta of Nusa Tenggara Barat. The Echinoidea were relatively common in the sea gras zone. On the basis of population density, Echinoidea was the dominant group and relatively highest in the individual density. In general the number of species of echinoderm fauna is smaller than in the Sekotong Lombok Barat Bay.